Effects of Trypanosoma brucei brucei on spatial learning and memory - Moses, Blessing (Department of Clinical Laboratory Sciences, 2023)
Human African trypanosomiasis (HAT), or sleeping sickness, is a sub-Saharan African disease caused by trypanosome parasites and transmitted through tsetse flies. The HAT is clinically defined by two diagnostic stages, commencing with an early-stage also known as the haemolymphatic stage where parasites appear to be localised in the blood and lymphatic systems, then a late-stage/ meningoencephalytic stage where the parasites are localised in the central nervous system. In the late stage, the parasite crosses the blood-brain barrier to disrupt the physiological function of the brain which results in marked sleep disorder. Studies on the Trypanosoma evansi infection mice model has shown that in addition to the sleep disorder caused by trypanosomiasis disease, learning and memory formation were impaired. Besides, only a little research has been conducted to validate this claim. Thus, this study aims to; i) understand the impact of behavioural Morris water maze (MWM) training test on immune cytokine levels in the brain with or without infection, ii) investigate the impact of Trypanosoma brucei brucei infection on spatial learning and memory, also, finally iii) evaluate infection severity with or without the behavioural training test. To address these objectives, three simultaneous studies were conducted whereby C57BL6 mice were grouped into four and two groups were infected with Trypanosoma brucei brucei. At first, we showed that the MWM training task did not affect the basal level of brain immune composition in naïve mice. Secondly, our result revealed that Trypanosoma brucei brucei infection resulted in spatial learning and memory impairment. Additionally, the consequential effect of infection resulted in an upregulated pro-inflammatory and antiinflammatory cytokine (IL-6, IFNγ, TNF, IL-10) immune response in the three brain areas of focus: the prefrontal cortex, hippocampus, and hypothalamus. Lastly, it was interesting to find that the MWM training task reduced the characteristic pathology associated with the disease. In conclusion, the study indicates that the increased immune cytokine composition in the brain above the basal level following Trypanosoma brucei brucei infection could contribute to the impairment in spatial learning and memory whereas, training during infection could potentially help to dampen the inflammatory and pathological severity of the disease.